Effect of Pumpkin Seed Extract (Cucurbita Moschata) on Premenstrual Syndrome Pain Intensity in Adolescent Girls - Farkhati Nafi'ah, Eka Apriadi; Sumarni, Sri; Windiarti, Sri Endang (JURNAL KEBIDANAN, 2025)
Premenstrual Syndrome is a condition commonly experienced by young women with physical and emotional symptoms that interfere with daily activities. The prevalence of PMS in Indonesia reaches 85% of the entire female population of reproductive age, consisting of 60-75% experiencing moderate and severe PMS. This study aimed to prove the effectiveness of pumpkin seed extract (Curcubita moschata) in reducing the level of Premenstrual Syndrome pain in young women. This quantitative research, using a True Experimental design, employed a pre-test and post-test with a control group design. The study population consisted of all young women experiencing premenstrual syndrome in the Semarang Ministry of Health Polytechnic area. The sampling technique used was a randomized clinical trial with 42 samples. Ethical approval from the Health Research Ethics Commission of Poltekkes Kemenkes Semarang with Number 1185/EA/F.XXIII.38/2024. The research was conducted on three treatment groups: intervention 1 with a dose of 500 mg 2x2 a day, intervention 2 with a dose of 500 mg 2x1 a day, and the control group which received starch tablets 500 mg 2x1 a day for 10 days. The results analyzed using the Paired T-Test showed that giving pumpkin seed extract at a dose of 500 mg 2x2 a day for 10 days could most significantly reduced the intensity of premenstrual syndrome pain (p-value 0.000; mean 3.86) compared to intervention 2 and control. These findings suggest that pumpkin seed extract has the potential to be an effective natural alternative for reducing PMS symptoms in adolescent girls, particularly in pain reduction.Â